Emerging pathogens in the fish farming industry and sequencing-based pathogen discovery. (October 2017) - Tengs, Torstein; Rimstad, Espen
Abstract: The use of large scale DNA/RNA sequencing has become an integral part of biomedical research. Reduced sequencing costs and the availability of efficient computational resources has led to a revolution in how problems concerning genomics and transcriptomics are addressed. Sequencing-based pathogen discovery represents one example of how genetic data can now be used in ways that were previously considered infeasible. Emerging pathogens affect both human and animal health due to a multitude of factors, including globalization, a shifting environment and an increasing human population. Fish farming represents a relevant, interesting and challenging system to study emerging pathogens. This review summarizes recent progress in pathogen discovery using sequence data, with particular emphasis on viruses in Atlantic salmon ( Salmo salar ). Highlights: Large-scale sequencing makes pathogen discovery possible without culturing or visual identification. Outbreaks of both established and emerging pathogens are associated with significant losses in the fish farming industry. Sequencing-based pathogen discovery has led to the description of several important viruses affecting farmed Atlantic salmon.